A comparison of different scores for diagnosis and mortality prediction of adults with sepsis in Low-and-Middle-Income Countries: a systematic review and meta-analysis. (December 2021) - Adegbite, Bayode R; Edoa, Jean R; Ndzebe Ndoumba, Wilfrid F; Dimessa Mbadinga, Lia B; Mombo-Ngoma, Ghyslain; Jacob, Shevin T; Rylance, Jamie; Hänscheid, Thomas; Adegnika, Ayola A; Grobusch, Martin P
Abstract: Background: Clinical scores for sepsis have been primarily developed for, and applied in High-Income Countries. This systematic review and meta-analysis examined the performance of the quick Sequential Organ Failure Assessment (qSOFA), Systemic Inflammatory Response Syndrome (SIRS), Modified Early Warning Score (MEWS), and Universal Vital Assessment (UVA) scores for diagnosis and prediction of mortality in patients with suspected infection in Low-and-Middle-Income Countries. Methods: PubMed, Science Direct, Web of Science, and the Cochrane Central Register of Controlled Trials databases were searched until May 18, 2021. Studies reporting the performance of at least one of the above-mentioned scores for predicting mortality in patients of 15 years of age and older with suspected infection or sepsis were eligible. The Quality Assessment of Diagnostic Accuracy Studies tool was used for risk-of-bias assessment. PRISMA guidelines were followed (PROSPERO registration: CRD42020153906). The bivariate random-effects regression model was used to pool the individual sensitivities, specificities and areas-under-the-curve (AUC). Findings: Twenty-four articles (of 5669 identified) with 27, 237 patients were eligible for inclusion. qSOFA pooled sensitivity was 0·70 (95% confidence interval [CI] 0·60–0·78), specificity 0·73 (95% CI 0·67–0·79), and AUC 0·77 (95% CI 0·72–0·82). SIRS pooled sensitivity, specificity and AUC were 0·88 (95% CI 0·79 -0·93), 0·34 (95% CI 0·25–0·44), and 0·69 (95% CI 0·50–0·83), respectively. MEWS pooled sensitivity, specificity and AUC were 0·70 (95% CI 0·57 -0·81), 0·61 (95% CI 0·42–0·77), and 0·72 (95% CI 0·64–0·77), respectively. UVA pooled sensitivity, specificity and AUC were 0·49 (95% CI 0·33 -0·65), 0·91(95% CI 0·84–0·96), and 0·76 (95% CI 0·44–0·93), respectively. Significant heterogeneity was observed in the pooled analysis. Interpretation: Individual score performances ranged from poor to acceptable. Future studies should combine selected or modified elements of different scores. Funding: Partially funded by the UK National Institute for Health Research (NIHR) (17/63/42).